(untitled) (Revisão de Sociologia Clínica, 2024)
Over the past quarter-century, The Magnolia Project has served a section of “the Northwest Corridor” of Jacksonville, FL, providing reproductive and well-woman care and intensive case management to reduce infant mortality in the African American community. During this time, the primary focus for Magnolia has been to provide clinic-based well woman care, prenatal care, support groups and case management through a store-front site in the heart of the target area. As new opportunities for funding became available, Magnolia moved from its “traditional” focus of women who come to, or are referred to, the clinic site to a broad-based Community-wide focus in order to address the underlying symptoms affecting the community’s health and the disparities this community faces. The Authors have been involved in the discussion, design, and implementation of Magnolia throughout the past 25 years, literally “sitting around the table” working on the original program proposal. In this paper we reflect on our role as evaluation partner for the Magnolia Project, and discuss how Program Representatives and staff, Evaluation Partners, and Community Partners joined forces over the past 25 years to implement the Magnolia project, and how they made a difference in their community. The lessons learned from this process are informative to other programs seeking to expand their community impact through partnering with university-based researchers.